2004
DOI: 10.2466/pms.98.3.999-1016
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Satiation Effect in Young and Older Adults

Abstract: Auditory and auditory+visual massed repetition served to examine semantic satiation in young and older adults and to understand the possible sources of this phenomenon. In Exp. 1, participants either heard or heard and saw prime words (ROYALTY) repeated 2, 15, or 30 times and made relatedness judgments on targets that were either semantically related (queen) or unrelated (box) to the repeated word. To distinguish satiation from general boredom, semantic satiation was operationally defined as a repetition-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Massed repetition of a single word, for example, impairs subsequent judgment of whether words fit the same semantic category (Smith, 1984;Smith & Klein, 1990;Pilotti, Antrobus, & Duff, 1997;Pilotti & Khurshid, 2004), decreases N400 effects (Kounios, Kotz, & Holcomb, 2000), and inhibits subsequent recall from memory (Kuhl & Anderson, 2011). Moreover, massed repetition of a single word or phrase can also lead to verbal transformations, as the word eventually turns into a variety of semantically and phonologically related words and nonwords (Warren & Gregory, 1958;Warren, 1961;Warren, 1968;Goldstein & Lackner, 1973;Kaminska & Mayer, 2002;Bashford, Warren, & Lenz, 2006;Bashford, Warren, & Lenz, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massed repetition of a single word, for example, impairs subsequent judgment of whether words fit the same semantic category (Smith, 1984;Smith & Klein, 1990;Pilotti, Antrobus, & Duff, 1997;Pilotti & Khurshid, 2004), decreases N400 effects (Kounios, Kotz, & Holcomb, 2000), and inhibits subsequent recall from memory (Kuhl & Anderson, 2011). Moreover, massed repetition of a single word or phrase can also lead to verbal transformations, as the word eventually turns into a variety of semantically and phonologically related words and nonwords (Warren & Gregory, 1958;Warren, 1961;Warren, 1968;Goldstein & Lackner, 1973;Kaminska & Mayer, 2002;Bashford, Warren, & Lenz, 2006;Bashford, Warren, & Lenz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This account is rendered plausible by several experimental paradigms which have demonstrated effects of verbal satiation on speech perception. Massed repetition of a single word, for example, impairs subsequent judgment of whether words fit the same semantic category (Pilotti, Antrobus, & Duff, 1997; Pilotti & Khurshid, 2004; Smith, 1984; Smith & Klein, 1990), decreases N400 effects (Kounios, Kotz, & Holcomb, 2000), and inhibits subsequent recall from memory (Kuhl & Anderson, 2011). Moreover, massed repetition of a single word or phrase can also lead to verbal transformations, as the word eventually turns into a variety of semantically and phonologically related words and nonwords (Bashford, Warren, & Lenz, 2006; Bashford, Warren, & Lenz, 2008; Goldstein & Lackner, 1973; Kaminska & Mayer, 2002; Warren, 1961; Warren, 1968; Warren & Gregory, 1958).…”
mentioning
confidence: 99%
“…In the verbal domain, repetition of vowel sequences leads to the perception of two voice streams uttering illusory syllables (Warren, 2008; Warren, Bashford, & Gardner, 1990; Warren, Healy, & Chalikia, 1996). If a word is repeated for longer than one minute, priming is inhibited, and listeners lose the sense of the meaning of the word as a result of semantic satiation (e.g., Cattaneo, Devlin, Vecchi, & Silvanto, 2009; Kounios, Kotz, & Holcomb, 2000; Pilotti & Khurshid, 2004; Smith, 1984). Additionally, verbal transformations may occur and listeners start to hear words that are actually not present in the acoustic signal (e.g., face, space, paste instead of pace , MacKay, Wulf, Yin, & Abrams, 1993; Warren, 1961, 1968; Warren & Gregory, 1958; for nonverbal stimuli, see Kaminska & Mayer, 2002).…”
mentioning
confidence: 99%
“…Turning to the effects of age, we did not find any differences between younger and older participants in illusion strength, and only a very small difference in response bias. Prior research has suggested that lexical node satiation decreases with age, as can be seen in decreased verbal transformation effects in older participants (Warren & Warren, 1966;Pilotti & Khurshid, 2004;Pilotti et al, 2011). This result suggests that individual differences in the readiness with which lexical nodes satiate is not a primary factor driving differences in perception of the song illusion in these stimuli.…”
Section: Discussionmentioning
confidence: 82%
“…A similar explanation has also been advanced for the verbal transformation effect, in which repetition of a word eventually leads to an unstable percept that swaps between different words with different meanings (Warren & Gregory, 1958): MacKay et al (1993) suggested that this illusion occurs when lexical nodes are satiated but phonological nodes remain activated. The verbal transformation effect is weaker in older participants (Warren & Warren, 1966;Pilotti & Khurshid, 2004;Pilotti, Simcox, Baldy, & Schauss, 2011), suggesting that satiation of lexical nodes due to repetition may be less rapid or less robust in older age. If so, then older participants may demonstrate less robust perception of the speech-tosong illusion as well.…”
Section: Introduction: Investigating Demographic Characteristics Driving Perception Of the Song Illusionmentioning
confidence: 94%